International PKM enhances the Study of the potential implementation of appropriate technology in Angkasa Malaysia cooperatives to improve education or campus cooperatives. - Febriana, Wiwit; Sukmareni; Meita Lefi Kurnia; Yunimar; Machdalena; Maidiawati; Yass Andria (Journal of Community Service and Application of Science, 2025)
The International Community Service Program (PKM) has become a strategic tool in identifying and encouraging the use of appropriate technology in the development of higher education cooperatives. This study aims to explore the potential implementation of appropriate technology in the management and operational systems of the ANGKASA Malaysia Cooperative as a model for developing campus cooperatives in Indonesia. Through an observational approach, semi-structured interviews, and institutional document review, empirical data were obtained regarding the digitalization and information systems engineering practices implemented by ANGKASA. The study results indicate that technology integration based on the needs of cooperative members can improve service efficiency, financial accountability, and academic community participation. These findings serve as important reflections for higher education cooperatives in Indonesia to adopt similar adaptive and sustainable systems. Therefore, synergy is needed between educational institutions, technology developers, and the government to strengthen the digital cooperative ecosystem on campus.